2011
DOI: 10.1007/s11300-011-0207-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Government Size and Trade Openness: Evidence from Pakistan

Abstract: Openness, Government size, Terms of trade volatility, C13, F41, H50,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…Regarding macroeconomic indicators, we find that inflation is negatively associated with public expenditure. These findings support those of Zakaria and Shakoor (2011) and Eterovic and Eterovic (2012) who argue that high inflation tends to reduce the real value of tax revenues, which can hamper the growth of government spending. The results also reveal no evidence that public debt and trade openness have a significant explanatory power.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Regarding macroeconomic indicators, we find that inflation is negatively associated with public expenditure. These findings support those of Zakaria and Shakoor (2011) and Eterovic and Eterovic (2012) who argue that high inflation tends to reduce the real value of tax revenues, which can hamper the growth of government spending. The results also reveal no evidence that public debt and trade openness have a significant explanatory power.…”
Section: Resultssupporting
confidence: 87%
“…The literature suggests that democracy favors the rising of public spending due to increased redistribution demands (Aidt et al, 2006), trade union pressure for wage increases (Rodrik, 1999) and the opportunistic behavior of politicians during elections (Drazen and Eslava, 2010). A number of explanatory variables are introduced into the equation: economic growth which leads to an increase in demand for public services (Adsera and Boix, 2002), the population growth which is assumed to have a negative effect on public consumption due to economies of scale (Alesina and Wacziarg, 1998), natural rents that are often used to finance public expenditure (Ross, 2001), public debt that has a crowding out effect on public expenditure (Mahdavi, 2004), inflation that can lead to a reduction in public spending due to the deterioration in the real value of tax revenues (Zakaria and Shakoor, 2011), and trade openness which can lead to lower taxes and thus decreasing spending (Schulze and Ursprung, 1999).…”
Section: Model Specificationmentioning
confidence: 99%
“…Macroeconomic policy theory decisively affects total government with PIP equal to 1, through inflation (P IP = 1) and FDI liabilities (P IP = 0.971). Consistent with Zakaria and Shakoor (2011), we find a negative effect of inflation on total expenditure. This can be explained by the shrinking size of the formal sector or the reductions of the real value of government revenues, which limit the government's ability to spend.…”
Section: Central Governmentsupporting
confidence: 83%
“…Results do not hold in every subsample. For example, Adams and Sakyi () find confirmatory evidence for sub‐Saharan Africa, Dahmardeh and Ahmadi () find confirmatory evidence for 12 Middle‐East countries, Hennessey () finds confirmatory evidence for Latin America, Zakaria and Shakoor () find confirmatory evidence for Pakistan, and Sáenz, Sabaté, and Gadea () find confirmatory evidence for Spain. On the other hand, Molana, Montagna, and Violato () do not find overwhelming support in a sample of 23 OECD countries, and Liberati () finds that the results are highly sample contingent.…”
Section: More Open Economies and Bigger Governmentsmentioning
confidence: 98%
“…Results do not hold in every subsample. For example, Adams and Sakyi (2012) find confirmatory evidence for sub-Saharan Africa, Dahmardeh and Ahmadi (2014) find confirmatory evidence for 12 Middle-East countries, Hennessey (2012) finds confirmatory evidence for Latin America, Zakaria and Shakoor (2011) find confirmatory evidence for Pakistan, and S aenz, Sabat e, and Gadea (2013) find 5 Alesina and Wacziarg (1998) confirmed the correlation but argue that country size is a mediating factor. Ram (2009) revisited this idea with panel data, and concluded that "the estimates are consistent with the possibility of a direct link between openness and government size along the lines suggested by Rodrik (1998)."…”
Section: Introductionmentioning
confidence: 95%